The Omar Story: The Role of Omars in Assessing Glacial History of West-Central North America - Prest, Victor; Donaldson, J.; Mooers, Howard (Géographie physique et Quaternaire, 2000)
AbstractThe direction of Wisconsinan glacial dispersion of distinctive Proterozoic erratics derived from the Belcher Group in southeastern Hudson Bay is shown to have been northwestward, westward and southward for hundreds of kilometres across Hudson Bay, Northern Ontario, western Canada, and several adjoining northern States. The most distinctive of these erratics, termed "omars", are composed of massive siliceous wacke characterized by buff-weathering calcareous concretions; these erratics were derived from the Omarolluk Formation of the Belcher Group, exposed in the Belcher Islands of eastern Hudson Bay, and probably underlying much of the southern part of this inland sea. Far less common but equally distinctive are erratics of red oolitic jasper that were derived from the Kipalu Formation of the Belcher Group. In parallel with the now widely accepted field term "omar", we introduce the term "kipalu" for such erratics of oolitic jasper. A map showing the distribution of the distinctive erratics, in relation to indicators of Wisconsinan glacier movement, provides the basis for inferring at least two discrete glaciations that produced several major ice lobes. This paper summarizes the field observations of numerous Canadian and American earth scientists, traces the evolution of thought on provenance of the distinctive erratics, and outlines the criteria for distinguishing "true" omars from erratics derived from other bedrock sources of concretion-bearing wackes.